Solve the following equation: 7x + 6 = -5x - 42

First, we gather like terms: 7x + 5x = -42 - 6 This gives: 12x = -48Now we can divide both sides by 12 to solve for x: 12x/12 = -48/12This gives: x = -4

Answered by Kyle Y. Maths tutor

3629 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Find the value of x in the equation 3x + 5 = 11


Prove that the square of an odd number is always 1 more than a multiple of 4.


Solve the equation 3(x+1) = 21


What is the easiest way to expand quadratic equations?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences